Innovation potential of regions in Northern Eurasia. - Stepan Zemtsov; Vyacheslav Baburin (European Regional Science Association (ERSA), 2013)
Northern territories (including the Arctic) occupy over 80% of Russian area. Development of these regions is based on ?resource? model, while other approaches have been ignored because of severe environmental conditions. The aim of this study was to assess an ability of northern regions to generate and diffuse innovations. The study was methodologically divided into three stages. The objective of the first and the second stage was to compare innovation capacities of northern and other Russian regions. An ability to create new knowledge is described by a number of indexes, the ability to extend and apply innovations - by a logistic function from model for innovation diffusion. This work confirmed the hypothesis of high concentration of the potential in major agglomerations and research centers, including Siberian cities: Tomsk, Novosibirsk, and Krasnoyarsk. Some arctic regions were characterized by high creative potential, but low rate of diffusion: Krasnoyarsk, Magadan, Sakha. The first fact can be explained by conservation of the Soviet scientific infrastructure and by initiative and mutual assistance of northern communities. The second fact is related to low population density and interaction. The key disadvantage of the method is in inadequate quality of Russian statistics. On the second stage, the authors identified innovation clusters in the sphere of environmental management. This sphere, connected with sustainable development, is a quickly developing innovative sector of economy, which includes remote sensing and GIS technologies, new technologies of exploration, hydro-meteorological and ecological modeling, etc. Leading university centers were identified by expert surveys and verified by ?Delphi? procedures. Centers had formed clusters, which were organized by principal of innovation cycle: fundamental and applied science, and enterprises. More than 30% of organizations were located in the northern regions. To classify the clusters the authors calculated an index of innovation capacity, which included the assessment of competence, new technologies and business-incubators, as well as the index of cohesion: connections and their structural and spatial diversity (Shannon's formula). Using graph theory techniques we identified interregional clusters of the Northern Periphery: Tyumen (Tyumen) and Siberian (Tomsk). Subsequent verification was carried out by analysis of publications and organizations? patent activity. The research shows that arctic regions are actively included in network with universities and science centers, serving as the main consumers of new technologies. Russian innovation space can be described by core-periphery model: the largest cities, located in the main strip of settlement, are the centers for generation and diffusion of innovation on the northern periphery. Emerging innovation clusters in the sphere of environmental management coincide with territorial structure of existing innovation space, but with significant northern bias. The study shows high innovation capacity of northern organizations in applying of new technologies.
Keywords: 330; Russia; regions; innovation; potential; clusters; northern communities